Use of an intraoperative navigation system for retrieving a broken dental instrument in the mandible: a case report. (December 2017) - Sukegawa, Shintaro; Kanno, Takahiro; Shibata, Akane; Matsumoto, Kenichi; Sukegawa-Takahashi, Yuka; Sakaida, Kyosuke; Furuki, Yoshihiko
Abstract Background A fracture of root canal instruments, with a fractured piece protruding beyond the apex, is a troublesome incident during an endodontic treatment. Locating and retrieving them represents a challenge to maxillofacial surgeons because it is difficult to access due to the proximity between the foreign body and vital structures. Although safe and accurate for surgery, radiographs and electromagnetic devices do not provide a precise three-dimensional position. In contrast, computer-aided navigation provides a correlation between preoperatively collected data and intraoperatively encountered anatomy. However, using a navigation system for mandible treatment is difficult as the mobile nature of the mandible complicates its synchronization with the preoperative imaging data during surgery. Case presentation This report describes a case of a dental instrument breakage in the mandible during an endodontic treatment for a restorative dental procedure in a 65-year-old Japanese woman. The broken dental instrument was removed using a minimally invasive approach with a surgical navigation system and an interocclusal splint for a stable, identically repeatable positioning of the mandible. Using the three-dimensional position of the navigation probe, a location that best approximated the most anterior extent of the fragment was selected. A minimally invasive vestibular incision was made at this location, a subperiosteal reflection was performed, and the foreign body location was confirmed using a careful navigation system. The instrument was carefully visualized and extruded from the apical to the tooth crown side and was then removed using mosquito forceps through the medullary cavity of the crown side of the tooth. Follow-up was uneventful; her clinical course was good. Conclusions The use of a surgical navigation system together with an interocclusal splint enabled the retrieval of a broken dental instrument in a safe and minimally invasive manner without damaging the surrounding vital structures.